Case Report: Unmasking the role of rem sleep in modulating non-convulsive status epilepticus in ring chromosome 20 syndrome: a genetic disorder of sleep architecture? - Mandato, Filippo; Di Claudio, Maria Teresa; Costantino, Umberto; Rovito, Francesca; Palumbo, Orazio; Palumbo, Pietro; La Neve, Angela; Pugliatti, Maura; Castori, M.; Carella, Massimo; d’Orsi, Giuseppe (Frontiers in Genetics, 2025)
Ring chromosome 20 syndrome (r (20)) is a rare genetic disorder characterized by drug-resistant epilepsy, cognitive impairment, and behavioral changes, often manifesting with non-convulsive status epilepticus (NCSE). We report a unique case of a 38-year-old woman with r (20) and recurrent NCSE, demonstrating a novel and striking electro-clinical correlation. Continuous video-EEG monitoring revealed distinct, alternating electro-clinical phases, with NCSE manifesting as continuous spike-wave during sleep (CSWS)-like patterns. Notably, the onset of REM sleep was consistently associated with a near-complete resolution of epileptiform abnormalities, followed by seizure-free awakening from REM. Intriguingly, the introduction of melatonin (4 mg/day) appeared to facilitate the attainment of REM sleep and was associated with a gradual reduction in NCSE frequency. This observation highlights the potential critical role of the neurophysiological state of REM sleep – characterized by cholinergic predominance and active GABAergic inhibition – in modulating and potentially suppressing the aberrant cortical excitability underlying NCSE in r (20). We hypothesize that the disrupted sleep architecture in r (20) may contribute to NCSE vulnerability, and that enhancing REM sleep dynamics could counteract this predisposition. The observed benefit of melatonin, potentially acting on MT1 receptors, warrants further investigation into targeted interventions aimed at normalizing sleep architecture, particularly REM sleep, as a novel therapeutic strategy for managing drug-resistant epilepsy and NCSE in r (20). This case underscores the importance of REM sleep in the context of epilepsy in r (20) and calls for future studies to elucidate the underlying mechanisms and confirm these findings in larger cohorts.